Efficiency of small-scale irrigation farmers in Northern Ghana: A data envelopment analysis approach - Adams, Abdulai; Balana, Bedru; Lefore, Nicole (SAGE Publications, 2020)
This study measures and explains technical efficiency (TE), economic efficiency and allocative efficiency of 110 small-scale vegetable farmers practicing various irrigation technologies for increased productivity. We employed the two-stage approach to estimate efficiency scores under constant returns to scale (CRS) and variable returns to scale (VRS) specifications. First, using a linear programming method, efficiency scores of the irrigated vegetable farmers were measured using the data envelopment analysis approach. The results show that about 27.3 per cent of the farmers currently operate on the production possibility frontier and are technically efficient, while 3.6 per cent were found to be both economically and allocatively efficient. The mean TE score for CRS was 50.6 per cent, compared with 78.1 per cent under the VRS. A Tobit regression at the second-stage analysis revealed that gender, experience, health and credit utilization have significant effects on TE. These results are valuable for stakeholders interested in promoting efficiency in smallholder irrigated production.JEL Classification: C14, C61, D24, D61, Q12